Community Response to Covid-19 Handling in Namorambe District, Deli Serdang Regency - patana, pindi (Journal of Saintech Transfer, 2021)
The spread of the Corona virus or better known as Covid-19 cannot be estimated when it will end. This condition is very concerning, including Indonesia, which has the highest death toll in Southeast Asia. This virus has also spread in North Sumatra including Deli Serdang Regency. One of the biggest challenges in mitigating Covid-19 is building public awareness about the importance of following the Covid-19 protocol in carrying out daily activities. Unfortunately, this condition is exacerbated by the low level of public awareness by ignoring health protocols during the pandemic period. It is hoped that the role of universities in educating the public can help prevent the spread of Covid-19 and increase community participation in mitigating efforts to prevent its spread. One of them is through community service activities by utilizing traditional ingredients for health drinks which are held at the Villa Mutiara Johor II Complex and its surroundings, Kec. Namorame, Deli Serdang Regency.